A critical cinema : interviews with independent filmmakers - MacDonald, Scott, 1942- (Berkeley : University of California Press, 1988)
Interviewees: Hollis Frampton -- Larry Gottheim -- Robert Huot -- Taka Iimura -- Carolee Schneemann -- Tom Chomont -- J.J. Murphy -- Vivienne Dick -- Beth B and Scott B -- John Waters -- Bruce Conner -- Robert Nelson -- Babette Mangolte -- George Kuchar -- Diana Barrie -- Manuel DeLanda -- Morgan Fisher
Includes bibliographical references and indexes.
Includes filmographies.
boek